1988
DOI: 10.1017/s0033822200044118
|View full text |Cite
|
Sign up to set email alerts
|

Improved Collagen Extraction by Modified Longin Method

Abstract: ABSTRACT. A re-evaluation of the Longin collagen-extraction method shows that a lower reflux temperature reduces degradation of protein ("collagen") remnants. This allows additional purification through ultrafiltration to isolate the >30kDalton fraction of the reflux product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
706
1
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 937 publications
(720 citation statements)
references
References 7 publications
4
706
1
9
Order By: Relevance
“…Collagen was extracted from some modern fishbones, as this is the material used for analyses of archaeological bones. A modified Longin-procedure with ultrafiltration was used [38][39][40]. The samples were converted to CO 2 by combustion in sealed evacuated quartz tubes containing CuO.…”
Section: Modern Plants and Animalsmentioning
confidence: 99%
“…Collagen was extracted from some modern fishbones, as this is the material used for analyses of archaeological bones. A modified Longin-procedure with ultrafiltration was used [38][39][40]. The samples were converted to CO 2 by combustion in sealed evacuated quartz tubes containing CuO.…”
Section: Modern Plants and Animalsmentioning
confidence: 99%
“…The sample was then gelatinized, following Longin (1971), in a pH3 solution at 75°C for 20h. The resulting gelatin was first filtered in an Eeze-Filter™ (Elkay Laboratory Products (UK) Ltd.) to remove small (<8m) particles and then through a 30 kDa ultrafilter (Sartorius "Vivaspin 15") (Brown, et al, 1988). Prior to use the filter was cleaned to remove carbon containing humectants (Brock, et al, 2007).…”
Section: Chronologymentioning
confidence: 99%
“…An additional cleaning of 'collagen' with base before extracting the gelatine fraction is used to dissolve and remove humic substances (Arslanov and Svezhentsev, 1993;Piotrowska and Goslar, 2002). Other methods involve removal of the light humic fraction (o30 kDa) using ultra filtration (Brown et al, 1988;Higham et al, 2006) or cleaning protein-remnants in ion-exchange columns (Law and Hedges, 1989). van Klinken et al (1994) showed that a separation of collagen specific peptides obtained from collagenase cleavage yields organic material that can be separated using chromatography (HPLC) and then AMS radiocarbon dated.…”
Section: Radiocarbon Dating Of Bonesmentioning
confidence: 99%